2018
DOI: 10.1039/c8ta01986j
|View full text |Cite
|
Sign up to set email alerts
|

Flexible cellulose nanopaper with high wet tensile strength, high toughness and tunable ultraviolet blocking ability fabricated from tobacco stalk via a sustainable method

Abstract: Retaining residual lignin in nanopaper leads to UV-blocking ability and significantly improves mechanical performance, especially the toughness and wet strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 60 publications
3
88
0
Order By: Relevance
“…bisporus fruiting body derived nanopapers (~87°) and cellulose nanopapers (~19-90° depending on their lignin content) [43][44][45] ( Figure 7). The hydrophobicity of mycelium-derived materials has previously been noted, with static water contact angles from 115-122° reported.…”
Section: Surface Properties Of the Nanopapersmentioning
confidence: 99%
“…bisporus fruiting body derived nanopapers (~87°) and cellulose nanopapers (~19-90° depending on their lignin content) [43][44][45] ( Figure 7). The hydrophobicity of mycelium-derived materials has previously been noted, with static water contact angles from 115-122° reported.…”
Section: Surface Properties Of the Nanopapersmentioning
confidence: 99%
“…Comparing to a reported work, it can be found that the Young’s modulus of AuNCs@CNF films had the comparative values than that of wound healing from various bacterial cellulose-based composites, which had the Young’s modulus of 4.2–6.1 GPa ( Ul-Islam et al, 2012 ) and 7.0 GPa ( Kim et al, 2011 ). In the present study, although the tensile strength of the AuNCs@CNF film was reduced with the increasing addition of AuNCs, the enhanced flexibility indicated that the AuNCs@CNF film possessed high folding strength, making it resistant to fracture (deformability) when used as the antibacterial film for application as the dressing over wound surface ( Li et al, 2018 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 57%
“…All AuNCs@CNF films showed the decreased tensile strength and tensile strain of 43.2–54.1 MPa and 4.1–4.7%, respectively. Typically, the tensile properties of the cellulose film are related to single fibrils and interfibrillar bonding, which are linked to the chemical composition, aspect ratio, and the added ingredient ( Wang et al, 2018 ; Imani et al, 2019 ). Moreover, the CNF films consisted of AuNCs at the concentration of 0.05–0.1 mM had the lower Young’s modulus (4.7–2.1 GPa) than that of neat CNF film (5.9 GPa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Among them, cellulose nanofibrils (CNFs)-based films have attracted remarkable attention for the controlled drug release, because CNFs have high aspect ratio, excellent mechanical properties, good biodegradability, and good cytocompatibility. [2,3] Moreover, the large amounts of hydroxyl or carboxyl groups are present on the surface of CNFs, which are appropriate for the formation of hydrogen bonds with hydrophilic drugs. [4][5][6][7][8][9] Biocompatibility is an important performance of the materials when used in drug application.…”
Section: Introductionmentioning
confidence: 99%